Probing halal food wisdom to the growth and development of spiritual intelligence / Shariffah Sallina Syed Ismail and Norliza Karia - Syed Ismail, Shariffah Sallina; Karia, Norliza (Academy of Contemporary Islamic Studies (ACIS), 2017)
Halal food contribution to the spiritual intelligence of human beings plays a crucial role in all domains. It also promote mental alertness, understanding and learning processes, physical well-being, emotional and spiritual health. This paper is a descriptive study focusing on the components and mechanism of halal food in order to gain knowledge of its spiritual values and wisdom for the phylogeny of human civilization, which has not previously revealed. “Therefore eat of what Allah has given you, lawful and good (things), and give thanks for Allah's favor if Him do you serve”. (Qur’an, 16: 114). Halal is an Arabic word termed as “lawful” and “pure” and it is the mechanism for the spiritual growth and development of human being. The findings indicate a substantial relationship between halal food and the ways human manage and govern the world.